PENERAPAN TUTOR SEBAYA UNTUK MENINGKATKAN FOKUS, KETELITIAN BELAJAR, DAN EMPATI SISWA SD - Syaikhu, Ach; Ghina, Nabila Nilna (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service activity aimed to implement a peer tutoring strategy as an effort to improve the quality of the learning process of elementary school students. The peer tutoring strategy was carried out by involving students who had a better understanding of the learning material to guide their peers during learning activities. The implementation method used Collaborative Action Research (CAR), which emphasizes collaboration between the community service team and the classroom teacher. The activity was conducted through several stages, including planning, implementation, and evaluation, which were carried out through observation of students’ learning activities and documentation of the program. The results showed that the peer tutoring strategy could be implemented effectively and had a positive impact on the learning process. Therefore, the peer tutoring strategy can be recommended as an effective, inclusive, and contextual alternative learning approach to support the improvement of learning quality and character development of elementary school students.